NANOPARTICLES MEASUREMENT IN ELECTRIC, GAS, AND DIESEL BUSES IN BOGOTÁ COLOMBIA MASS TRANSPORTATION SYSTEM - Vargas, Diego; Galvis, Boris; Durán, Vanesa (TECCIENCIA, 2024)
The sustainability for urban contexts is a very important objective today, and it needs to be linked transversally to all processes of technological change that impact people and the territory. In this study, we compare the nanoparticles measured inside diesel, gas, and electric buses during their normal operation in Bogota, Colombia. We used a miniature diffusion size classifier (DiSCmini) to measure nanoparticles concentrations, average particle size, and lung-deposited surface area. Our results revealed significantly lower levels of this pollutant inside electric buses. The concentration of nanoparticles per cubic centimeter is about 41% and 27% lower in electric buses compared to diesel and gas respectively. The lung-deposited surface area is also lower in electric buses. Nevertheless, average particle size in electric buses is 10% and 18% smaller compared to diesel, and gas respectively. The results of this study are important because they show useful information for future selection processes of bus technologies for public passenger transport in other cities around the world; This research provides information resources that can be used in technical evaluation processes that link the possible effects on the health of users and the environment, and favor concepts for the improvement of sustainability.